2021
DOI: 10.3390/ijms222312702
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyogenic Differentiation Potential of Human Dilated Myocardium-Derived Mesenchymal Stem/Stromal Cells: The Impact of HDAC Inhibitor SAHA and Biomimetic Matrices

Abstract: Dilated cardiomyopathy (DCM) is the most common type of nonischemic cardiomyopathy characterized by left ventricular or biventricular dilation and impaired contraction leading to heart failure and even patients’ death. Therefore, it is important to search for new cardiac tissue regenerating tools. Human mesenchymal stem/stromal cells (hmMSCs) were isolated from post-surgery healthy and DCM myocardial biopsies and their differentiation to the cardiomyogenic direction has been investigated in vitro. Dilated hmMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Muscle structure and increased expression of cardiogenic differentiation markers were observed in transduced cells (Neshati et al, 2018). The combination of HDAC inhibitor SAHA and biomimetic matrix collagen I‐based hydrogels or incorporation of vascular endothelial growth factor (VEGF) into nanofibers increases the potential of hMSCs to differentiate into cardiomyocytes (Kai et al, 2017; Miksiunas et al, 2021) and accelerates differentiation by altering cell adhesion or matrix hydrogel carrier (Li, Guo, et al, 2012; Roberts et al, 2016) (Figure 2). Some studies have also shown that MSCs predifferentiated into cardiomyocytes have better cardiac regeneration ability than undifferentiated MSCs injected into the heart (Guan et al, 2011).…”
Section: Cell Therapy For Heart Regenerationmentioning
confidence: 99%
“…Muscle structure and increased expression of cardiogenic differentiation markers were observed in transduced cells (Neshati et al, 2018). The combination of HDAC inhibitor SAHA and biomimetic matrix collagen I‐based hydrogels or incorporation of vascular endothelial growth factor (VEGF) into nanofibers increases the potential of hMSCs to differentiate into cardiomyocytes (Kai et al, 2017; Miksiunas et al, 2021) and accelerates differentiation by altering cell adhesion or matrix hydrogel carrier (Li, Guo, et al, 2012; Roberts et al, 2016) (Figure 2). Some studies have also shown that MSCs predifferentiated into cardiomyocytes have better cardiac regeneration ability than undifferentiated MSCs injected into the heart (Guan et al, 2011).…”
Section: Cell Therapy For Heart Regenerationmentioning
confidence: 99%
“…We demonstrated that such substrates can be efficiently used for the covalent immobilization and patterning of different proteins. Covalent immobilization of Fn in micropatterns with a high density of molecules in a hydrogel-like state has proved useful, for example, in studies of human primary cardiac stem cell differentiation [18]. Therefore, in the present study, we report on the possibility of fabricating biochip surfaces consisting of FnIII9-10 or FnIII10 covalently immobilized on a chemically activated PEG MA surface by microcontact printing [19].…”
Section: Introductionmentioning
confidence: 98%
“…Histone deacetylase (HDAC) inhibitors affect various cellular signals, such as cell proliferation, terminal differentiation, apoptosis, cell homeostasis, cell cycle arrest, and gene expression [ 1 , 2 ]. When histone acetyltransferase (HAT) transfers the acetyl groups of acetyl-CoA to the lysine residues in the NH 2 terminal tails of core histones, the chromosome is uncoiled into chromatin, making transcription easier [ 3 ]. When HDACs remove the acetyl group, the chromatin condenses back into a chromosome [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%